Severe burn injury: Body Mass Index and the Baux score. Issue 1 (February 2021) - Saadat, Ghulam H; Toor, Rubinder; Mazhar, Faizan; Bajani, Francesco; Tatebe, Leah; Schlanser, Victoria; Kaminsky, Matthew; Messer, Thomas; Starr, Frederic; Dennis, Andrew; Poulakidas, Stathis; Bokhari, Faran
Highlights: Data suggest negative relationship between body mass index and mortality among burn patients Preobesity appears to have a protective role in burn Body mass index was not found to be valuable in Baux Index. Abstract: Objective: The revised Baux score (age total body surface area (TBSA) burned and inhalation injury)) is predictive of mortality in burn patients. Our study objective was to assess whether the addition of body mass index (BMI) to the revised Baux score would be of value. We posited that increasing BMI follows a pattern similar to age and TBSA in the revised Baux score after severe burn injury. Methods: Patient data from the burn registry was queried for patients admitted between 1/1/2013 to 8/31/2019. Patients 12 years or older with a TBSA of 20% or greater burn were included. Inpatient outcomes were analyzed based on BMI. Results: 56 of 1365 patients met inclusion criteria. Mean age of the study population was 48.25 years and 64.3% of patients were male. Median BMI was 25.8 and median TBSA was 26.5. Inhalation injury was present in 44.6% (25/56) of patients. Median hospital length of stay (LOS) and ICU LOS were 21.5 and 17 days respectively. On bivariate analysis, non-survivors had higher TBSA (41.5% vs 25.5%, p = 0.034), more inhalation injury (83.3%, 10/12 vs 34.8%, 15/43 p = 0.003) and higher complication rates (91.6%, 11/12 vs 59.1 %, 25/43, p = 0.043). Survivors also had higher BMI (28.2 vs 23, p = 0.003) and increased hospital LOS (24 vs 5.5, p = 0.003). Automatic model fit in binary logistic regression showed a negative relationship between BMI and mortality. Conclusion: We found a negative relationship between BMI and mortality. Pre-obesity appears to have a protective role, but BMI was not found to be a useful addition to the revised Baux score. Larger sample sizes may be of benefit a for a for a more definitive understanding of the role of BMI with regards to burn survival.